Early Childhood Development and Skills across the Life-Course through the Lens of the Developing Brain - Chapko, Dorota (World Bank, Washington, DC, 2016)
Human development and development are inseparable, and now new evidence emerges that brain development is the key driving mechanism behind this association. The foundations of brain architecture are established early in life. Critical aspects of its structure begin to be shaped by experience before and soon after birth. The current report discusses brain development from a life-course perspective with a particular emphasis on early childhood development (ECD), skills formation, resilience, and aging. There is mounting evidence that early and sustained investments in brain development have economic and social returns that can benefit current and future generations. This paper synthesizes knowledge across multiple disciplines and is weighted towards findings from brain sciences to encourage a new perspective on human development initiatives among policy makers and international development practitioners. The report discusses the role of social policies in shaping brain function and structure. The policy-relevant findings from brain sciences research can greatly enhance the ability to carry out cost-effective policies that foster human development over the life-course, eliminate extreme poverty, and improve shared prosperity.